# How do you solve 3x + 3(x - 2) - 12 = -24?

Jun 17, 2017

See a solution process below:

#### Explanation:

First, expand the terms in parenthesis by multiplying the terms within the parenthesis by the term outside the parenthesis:

$3 x + \textcolor{red}{3} \left(x - 2\right) - 12 = - 24$

$3 x + \left(\textcolor{red}{3} \cdot x\right) - \left(\textcolor{red}{3} \cdot 2\right) - 12 = - 24$

$3 x + 3 x - 6 - 12 = - 24$

$\left(3 + 3\right) x + \left(- 6 - 12\right) = - 24$

$6 x + \left(- 18\right) = - 24$

$6 x - 18 = - 24$

Next, add $\textcolor{red}{18}$ to each side of the equation to isolate the $x$ term while keeping the equation balanced:

$6 x - 18 + \textcolor{red}{18} = - 24 + \textcolor{red}{18}$

$6 x - 0 = - 6$

$6 x = - 6$

Now, divide each side of the equation by $\textcolor{red}{6}$ to solve for $x$ while keeping the equation balanced:

$\frac{6 x}{\textcolor{red}{6}} = - \frac{6}{\textcolor{red}{6}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{6}}} x}{\cancel{\textcolor{red}{6}}} = - 1$

$x = - 1$